EVALUASI KEBIJAKAN RETRIBUSI TEMPAT REKREASI DI KABUPATEN KUDUS - Galuh Putri Cahyani; Aufarul Marom (Journal of Public Policy and Management Review, 2017)
As the development of era, levies cost of recreation area continues to grow, it also necessary need improvement and development of recreation area. Levies are set to be in accordance with the conditions and needs of the community, in the levies set in Regulation Kudus District Number 13 In 2015 about Retribution Recreation and Sport (Peraturan Daerah Kabupaten Kudus Nomor 13 Tahun 2015 tentang Retribusi Tempat Rekreasi dan Olahraga). That levies are used for improvement of recreation area’s services to community also support the improvement of locally-generated revenue. This study aims to determine policies of recreation area levy in improving service facilities of recreation area in Kudus district also to determine inhibiting and supporting factors from policies of recreation area levy in Kudus district. This research is a descriptive study using a qualitative approach with interviews of informants. Based on the research that has been done stated there are still some things that hinder in recreation area levies, that caused by a lack of personnel or it’s human resource, beside that financial problems causing difficulties to perform maintenance and make development innovations. This study resulted in feedback to the government in achieving success to perform maintenance for current facility, increasing the number of personnel or skilled human resources not only the labor resource to improve its quantity and quality also the most important part is the coordination between the relevant government.